2007
DOI: 10.1375/twin.10.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Young Netherlands Twin Register (Y-NTR): A Longitudinal Multiple Informant Study of Problem Behavior

Abstract: The Netherlands Twin Register (NTR) was established around 1987 at the Vrije Universiteit in Amsterdam, the Netherlands. The current article summarizes the longitudinal genetic analyses of maternal and paternal ratings of twins' behavior as a function of the sex of the children for the traits of aggression (AGG), attention problems (AP), anxious/depression (ANX), internalizing behavior (INT) and externalizing behavior (EXT). We found that genetic influences are the most important factor in explaining individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
120
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 13 publications
2
120
0
Order By: Relevance
“…30 We were particularly interested whether there would also be a difference in BMI between adolescent twins and siblings. Indeed, siblings had a higher BMI than twins in the questionnaire sample, but in contrast to the test protocol sample, siblings were slightly taller than twins.…”
Section: Discussionmentioning
confidence: 99%
“…30 We were particularly interested whether there would also be a difference in BMI between adolescent twins and siblings. Indeed, siblings had a higher BMI than twins in the questionnaire sample, but in contrast to the test protocol sample, siblings were slightly taller than twins.…”
Section: Discussionmentioning
confidence: 99%
“…A number of quantitative genetic studies have examined problem behavior in children with the CBCL, with the main focus on internalizing and externalizing behavior problems (Bartels et al, 2004a;Bartels et al, 2004b;Bartels et al, 2007;Edelbrock et al, 1995;Gjone & Stevenson, 1997;Hudziak et al, 2000;Leve et al, 1998;Schmitz & Mrazek, 2001;Silberg et al, 1994;Van den Oord et al, 1995;Van der Valk et al, 1998;Zahn-Waxler et al, 1996) and a number of these studies have modeled the agreement and disagreements among parental reports. For example, in a study by Rowe and Kandel (1997), parents rated the internalizing and externalizing behavior of their two oldest children (between 9 and 17 years old).…”
mentioning
confidence: 99%
“…Hewitt et al, (1992) studied internalizing behavior in prepubertal (8-11 years) and pubertal twins (12-16 years), and found evidence for such genetic effects. Dutch twin studies on internalizing and externalizing behaviors also found that the unique viewpoint of parents does not solely reflect rater bias (Bartels et al, 2003;Bartels et al, 2004a;Bartels et al, 2007;Van der Valk et al, 2001;Van der Valk et al, 2003).…”
mentioning
confidence: 99%
“…Importantly, the pattern of non-response did not differ between MZ and dizygotic (DZ) mothers. For internalizing and externalizing problems, Bartels et al (2007) compared the level of problem behaviors in 3-year-old twins between three groups: a group that participated at ages 3, 7, 10, and 12, a group that participated only at age 3, and a group with temporary non-participation. No significant mean differences in externalizing and internalizing behavior problems were found between the three groups.…”
Section: Longitudinal Survey Datamentioning
confidence: 99%
“…They are distinguished by recruitment and ways of data collection. Twins participating in the YNTR are registered at birth by their parents, and are recruited with the help of a commercial baby organization that visits parents of newborns and the 'Dutch association for parents of multiples' (NVOM; Bartels et al, 2007;Boomsma et al, 2002). The data collection for the YNTR and ANTR differs, simply because as long as twins are under age 14 their parents and their teachers are the main informants, whereas at later ages, the data are collected through self-reports.…”
mentioning
confidence: 99%